Argentine ant, Linepithema humile (Mayr) (Insecta: Hymenoptera: Formicidae) - Katherine Carroll; Adam Dale (EDIS, 2021)
The Argentine ant, Linepithema humile (Mayr), is an insect native to South America, but an invasive species in many parts of the world. It is globally distributed. Linepithema humile is considered a pest species, primarily due to its feeding habits of tending and protecting honeydew producing insects, such as scale insects, which are often damaging to crops and ornamental plants. This aggressive, populous ant species also has a negative effect on native ant species. Linepithema humile colonies have multiple queens, allowing colonies to grow and spread rapidly. Under certain conditions, the argentine ant may also become a household pest if it finds a way into homes. Linepithema humile has been designated as a tramp ant species, meaning that it has an incredible ability to spread and establish in new areas and is difficult to control. Linepithema humile, like other tramp species, can establish in new locations quickly due to the multi-queen nature of the colonies, their abitlity to forage and find resources, and the extensive network of interrelated colonies they are able to form. This document provides an in-depth synopsis of the insect's life history, biology, and management.